2004
DOI: 10.1111/j.1365-2141.2004.04857.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of highly purified CD34+ progenitor cells from alternative donors in children with refractory severe aplastic anaemia

Abstract: Summary Without transplantation from a human leucocyte antigen‐identical family donor, refractory severe aplastic anaemia (SAA) has an unfavourable prognosis. Conventional transplantation from a matched unrelated donor carries a high rate of mortality. We transplanted large numbers of highly purified CD34+ cells from matched unrelated (n = 4), mismatched unrelated (n = 4) and mismatched related (n = 1) donors into nine children with refractory SAA. The grafts consisted of granulocyte colony‐stimulating factor‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…25 Other studies have reported outcome in patients with SAA transplanted from donors other than HLA-identical siblings using registry data, with survival probabilities of approximately 35%. 11 Some series have reported better results, 19,[26][27][28][29][30][31][32] for example, in a recent Japanese study of 154 patients showing overall survival of 56%. 26 Donorrecipient HLA disparity was determined using highresolution techniques, but donor-recipient compatibility was not a significant factor in this study.…”
Section: Discussionmentioning
confidence: 99%
“…25 Other studies have reported outcome in patients with SAA transplanted from donors other than HLA-identical siblings using registry data, with survival probabilities of approximately 35%. 11 Some series have reported better results, 19,[26][27][28][29][30][31][32] for example, in a recent Japanese study of 154 patients showing overall survival of 56%. 26 Donorrecipient HLA disparity was determined using highresolution techniques, but donor-recipient compatibility was not a significant factor in this study.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Conditioning regimen There are only a few publications on childhood alternative donor transplants in SAA, and most cohorts are very small. Kojima et al 18 reported on 15 children grafted with unmanipulated marrow from serologically matched unrelated donor after conditioning with CY, anti-thymocyte globulin and TBI 5 Gy.…”
Section: Donor Selectionmentioning
confidence: 99%
“…19 Other approaches have been to use alemtuzumab instead of ATG in an otherwise similar regimen to EBMT, 25 or G-CSF-mobilized CD34 + -selected PBSC. 26 However, both these latter approaches require further evaluation in larger studies.…”
Section: Matched Unrelated Donor Bmtmentioning
confidence: 99%